Tree species Diversity in Narepally Reserve Forest Hyderabad, Telangana - Jones, Shiphra; Ammani, K. (Indian Forester, 2025)
Biodiversity conservation is the need of the hour due to increasing threats from anthropogenic impacts. The vulnerability of species and biodiversity in general, affecting ecological balance and environmental quality, is also increasing day by day. Trees are unique in terms of development, sustainability, and longevity, with a lifespan in the living world reaching up to several years. The main aim of this study is to analyse the diversified composition of tree flora in the Narepally Reserve Forest, Hyderabad, Telangana, India, through field data collection from July 2022 to September 2023. A total of 69 tree species belonging to 25 families and 54 genera were enumerated in the study of which 01 is EN, 03-VU, 02-NT, and 32-LC are tree species under the IUCN Red List Criteria. Protection of this reserve forest is essential to conserve the native plant species of this ecologically important forest area.